EFFECT OF FORCE MOLTING USING HIGH LEVELS OF DIETARY NANO ZINC OXIDE ON PRODUCTIVE PERFORMANCE OF LAYING HENS - Al-Mosawy, H.A.; Al-Hassani, D.H (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The experiment was conducted during 1/4/2020-7/31/2020 to study the effect of adding high levels of nano-zinc oxide with the diet to induce force molting in laying hens by measuring some productivite traits. Eighty laying hens, 69 weeks old were used, randomly divided into four treatments, five replicates for each treatment using CRD.  Experimental treatments were: first treatment (T1), second treatment (T2), third treatment (T3) and fourth treatment (T4), which means control treatment without molting, adding 10, 15, and 20 gm of nano-zinc oxide / kg feed respectively. Results showed significant decreases (P